Analisis Dampak Pemotongan Gaji untuk Wakaf terhadap Perilaku Aparatur Sipil Negara - Ratna Dewi; Neng Kamarni; Fery Andrianus (SAFE-Network, 2022)
The Ministry of Religion as a government institution is the main driving force in implementing government programs in the social and religious fields through carrying out the National Cash Waqf Movement (GNWU). Employees at the ranks of ministries consistently and measurably always carry out programs announced by the government in waqf. Waqf money is an alternative instrument to drive the community's economy in overcoming poverty and income inequality and strengthening social solidarity and a sense of concern in the community. This study analyzes the impact of cutting wages for waqf on the behavior of the State Civil Apparatus (ASN). The ASNs studied were employees who served at the Ministry of Religion in Padang City. Salaries are deducted directly in the form of cash waqf or al-nuqud waqf. Waqf obligations are deducted in the form of money against individuals directly. This study uses primary data obtained through distributing questionnaires and conducting several in-depth interviews with respondents. The number of respondents was 285 people in the State Civil Apparatus of the Ministry of Religion of Padang City. The analysis tool used is SEM-PLS. The results of this study found that the variables of attitude, subjective norms and religiosity had a positive and significant effect on the behavior of civil servants at the Ministry of Religion of Padang City conducting cash waqf through salary deductions.